Relationship between Memory Strategies and Motor Symptoms in Parkinson's Disease - Berger, Hans J.C.; van Es, Nelleke J.C.; van Spaendonck, Karel P.M.; Teunisse, Jan-Pieter; Horstink, Martin W.I.M.; van 't Hof, Martin A.; Cools, Alexander R. (Journal of clinical and experimental neuropsychology, 1999)
Patients with Parkinson's disease(PD) show a serious decrease in performance on tasks which lack explicit guidelines and which necessitate the subject to develop his or her own strategy. Using the California Verbal Learning Task(CVLT) we have found evidence that this phenomenon becomes also manifest in learning and memory. The goal of the present study on PD was to investigate whether or not there is an intrinsic relationship between PD-specific deviant learning characteristics and the severity of motor symptomatology. The results show, as expected, a significant correlation between the severity of bradykinetic/hypokinetic symptoms and the serial clustering gradient of the CVLT: the more bradykinetic PD patients (n = 48) were, the more they were dependent on the externally guided serial learning strategy. The findings are discussed in the context of our hypothesis that the actual deficit in patients with PD is a deficient processing of ambiguous internal cues.